2022
DOI: 10.1016/j.sleepx.2022.100042
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep deprivation and arterial pressure variations: a systematic literature review

Abstract: Objectives Arterial hypertension is a cardiovascular disease defined as a sustained high blood pressure, constituting an important risk factor for the development of heart diseases, such as coronary heart disease and heart failure. At the same time, pathophysiological pathways underlying sleeping deprivation provides biological plausibility for a causation connection between sleep deprivation and acute or chronic blood pressure elevation, such as the mechanism behind blood pressure dipping at nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To date, studies concerning sleep deprivation and inflammatory cytokines remain elusive. Sleep deprivation indeed increases the main stress hormone, cortisol, which plays a role in various disease development, such as hypertension and cardiovascular disease (Sá Gomes e Farias et al, 2022). On the other hand, some studies indicated that people with sleep disorders showed an alteration in circulating levels of TNF-α and IL-6.…”
Section: Results S and Discussionmentioning
confidence: 99%
“…To date, studies concerning sleep deprivation and inflammatory cytokines remain elusive. Sleep deprivation indeed increases the main stress hormone, cortisol, which plays a role in various disease development, such as hypertension and cardiovascular disease (Sá Gomes e Farias et al, 2022). On the other hand, some studies indicated that people with sleep disorders showed an alteration in circulating levels of TNF-α and IL-6.…”
Section: Results S and Discussionmentioning
confidence: 99%
“…AF, as the most common arrhythmia in clinical practice, has been associated with increased morbidity, mortality, and healthcare burden [33]. Recent studies suggested the importance of sleep disturbance in regulating the process of risk factors for AF development, including hypertension, heart failure, diabetes, and obesity [4][5][6]33], all of which correspond to GM dysbiosis [34]. Meanwhile, the direct interaction between disordered GM and AF has been confirmed [17].…”
Section: Discussionmentioning
confidence: 97%
“…Sleep disturbance may lead to learning disabilities in children, memory impairment in people of all ages, and personality changes and depression [1][2][3]. It may also increase the risk of multiple diseases, including damage to the cardiovascular system [4][5][6]. Moreover, a recent cohort study revealed that night shift work is associated with the risk of atrial fibrillation (AF) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this intensification would at least partially compensate for the disturbance of postural balance resulting from the lack of sleep. However, Sá Gomes e Farias et al (2022) observed that sleep deprivation was associated with an increase in muscle sympathetic nervous activity. Due to its excitatory effects, cardiac, vascular, and respiratory muscles are more strongly activated, i.e., modulation of peripheral vascular resistance, venous return, heart rate, contractility, and cardiac output as well as respiratory variables ( Sá Gomes e Farias et al, 2022 ).…”
Section: Effects Of Sleep Deprivation On the Different Systems Of The...mentioning
confidence: 99%
“…However, Sá Gomes e Farias et al (2022) observed that sleep deprivation was associated with an increase in muscle sympathetic nervous activity. Due to its excitatory effects, cardiac, vascular, and respiratory muscles are more strongly activated, i.e., modulation of peripheral vascular resistance, venous return, heart rate, contractility, and cardiac output as well as respiratory variables ( Sá Gomes e Farias et al, 2022 ). All these factors amplify the internal reaction forces that constitute internal mechanical stimuli and contribute to small continuous segmental displacements and thus disturb postural balance ( Conforto et al, 2011 ).…”
Section: Effects Of Sleep Deprivation On the Different Systems Of The...mentioning
confidence: 99%